(untitled) (Journal of Analytical Oncology, 2013)
Background: Urinary tract lithiasis(UTL) requires careful intervention, especially when associated with other diseases. The purpose of this study was to assess the outcome of symptomatic UTL in children with acute lymphoblastic leukemia (ALL) and to evaluate its correlation with the anti-neoplastic treatment phase and drugs, and to assess the need for intervention, results, complications and follow-up. Procedure: The charts of 350 patients with ALL (1990-2008) were retrospectively evaluated. Signs and symptoms, methods of diagnosis, complications, treatment approach, resolution, anti-leukemic treatment phase when the UTL was diagnosed, drugs used and interference on ALL treatment were recorded. Results: A total of 12/350 patients (3.4%) had UTL (14 stones). The median age was 7.6 years. Pain was present in 60%, hematuria in 20% and both in 20%. The median stone size was 4mm (3- 13.8mm). Three patients required hospitalization (pain) and one had chemotherapy discontinued due to severe hematuria and blood support. At the time of diagnosis of UTL, four patients were in the induction phase with corticosteroids, four were in the maintenance phase with corticosteroids, two were in the maintenance phase without corticosteroids, and one had a recurrence after therapy, and two were off-therapy. 11/13 episodes of UTL had spontaneous resolution, two underwent successful extracorporeal shockwave lithotripsy, and one patient remains with an asymptomatic stone. Conclusions: 3.4% of children with ALL presented symptomatic UTL. While the majority of cases have been resolved spontaneously, hospitalization and delay in chemotherapy have increased morbidity in these children.